Galileo: orologi atomici e ridondanze - Pititto, Gianluca (GEOmedia, 2017)
Galileo atomic clocks and redundancies. Some malfunction on board of Galileo satellites are likely to affect the results of the satellite positioning system. The contingent problems upon the proper functioning of the system's high-tech equipment, in particular atomic clocks, could be responsible for the loss of accuracy of the navigation data.